FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - A, Dea Monica; Nafi’ah, Zumrotun; Lutfiana, Lina (STIE Semarang, 2024)
Company debt policy is an action by company management that will fund company operations using capital derived from debt. Debt policy describes the total long-term debt owned by the company to finance the company's operational activities. The aim of this research is to determine the influence of company size, liquidity, profitability and company growth on debt policy in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023. The population in this research is food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2019 - 2023, totaling 130 companies. The sample in this study used a purposive sampling method so that a sample of 70 was obtained. The independent variables in this study were company size, liquidity, profitability and company growth, while the dependent variable in this study was debt policy. The analytical method used is multiple linear regression test. The results of this research show that company size has a significant effect on debt policy with a significance of 0.005 <0.05. Liquidity has no significant effect on debt policy with a significance of 0.143 > 0.05. Profitability has a significant effect on debt policy with a significance of 0.000 < 0.05. Company growth does not have a significant effect on debt policy with a significance value of 0.908 > 0.05. The coefficient of determination (adjusted R Square) is 0.318. This means that the variables company size, liquidity, profitability and sales growth have a role of 31.8% in being able to explain or explain the debt policy variable. For investors to pay more attention to company size and profitability variables, company management needs to pay attention to company performance and evaluate it in relation to debt policy.